2019
DOI: 10.31688/abmu.2019.54.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dietary minerals intake of children with early childhood caries

Abstract: Étude sur la consommation alimentaire de minéraux chez les enfants atteints de carie dentaire dans la petite enfance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Dental caries management by risk assessment in children (Dobrinka Mitkova Damyanova) 41 Microbiological studies of randomly collected plaque biofilm samples removed from dental crowns and during polishing showed that in the oral cavity, the most common oral bacteria in dental plaque was Streptococcus mutans, followed by Streptococcus sobrinus [V. Kim Kutsch 2014] [22], [23]. The risk of developing dental caries is generally associated with only a few common factors, and these factors lead to general patterns of dental disease [24], [25]. Modern strategies can be organized into three categories.…”
Section: Issn: 2252-8806 mentioning
confidence: 99%
“…Dental caries management by risk assessment in children (Dobrinka Mitkova Damyanova) 41 Microbiological studies of randomly collected plaque biofilm samples removed from dental crowns and during polishing showed that in the oral cavity, the most common oral bacteria in dental plaque was Streptococcus mutans, followed by Streptococcus sobrinus [V. Kim Kutsch 2014] [22], [23]. The risk of developing dental caries is generally associated with only a few common factors, and these factors lead to general patterns of dental disease [24], [25]. Modern strategies can be organized into three categories.…”
Section: Issn: 2252-8806 mentioning
confidence: 99%